Teknik Permainan Beatbox Flute Dalam Box Karya Christopher Kuhns - Said, Arini Nur; Limbong, Helena Evelin (Institut Seni Indonesia Yogyakarta, 2021)
The composition of solo flute created by Christopher Kuhns entitled ‘BOX’ is interesting because it uses beatbox tecnique in playing the flute. beatbox technique in flute is not a new technique for flute, Greg Pattillo is one of the flutist has introduced this technique in 2009. This research aims to describe the beatbox flute technique used in Box coposition and how to produce beatbox technique through articulation and tonguing in flute. The method used by researcher is a qualitative descriptive research methode with a analysis approach. The data obtained though literature studies, music score of Box, collecting audio-visual documentation in the form of performing Box composition through the internet and interview with Christopher Kuhns, Greg Pattillo, and Willem Carolus Cristopherson Tamnge. The result of this research show that the flute not only can produce melodic sounds, but also can produce percussive sounds with many sound colors. Beatbox technique was imitating percussion sound such as; bass drum, hi-hat, and snare. In Box Composition, there are seven beatbox articulation techniques, such as classic kick, closed k hi-hat, closed t hi-hat, meshed snare, open t hi-hat, shaker, and classic inward snare. The flute articulation techniques are accent, legato, staccato, and slur, also tonguing techniques used in Box composition are single tonguing and double tonguing. The application of articulation and tonguing influence each other in beatbox flute palying to produce clear melody and rhythm.